Lentiviral silencing of GSK-3β in adult dentate gyrus impairs contextual fear memory and synaptic plasticity - Chew, Benjamin; Ryu, Jae Ryun; Ng, Teclise; Ma, Dongliang; Dasgupta, Ananya; Neo, Sin Hui; Zhao, Jing; Zhong, Zhong; Bichler, Zoë; Sajikumar, Sreedharan; Goh, Eyleen L. K. (Frontiers in Behavioral Neuroscience, 2015)
Attempts have been made to use glycogen synthase kinase-3 beta (GSK3β) inhibitors for prophylactic treatment of neurocognitive conditions. However the use of lithium, a non-specific inhibitor of GSK3β results in mild cognitive impairment in humans. The effects of global GSK3β inhibition or knockout on learning and memory in healthy adult mice are also inconclusive. Our study aims to better understand the role of GSK3β in learning and memory through a more regionally, targeted approach, specifically performing lentiviral-mediated knockdown of GSK3β within the dentate gyrus (DG). DG-GSK3β-silenced mice showed impaired contextual fear memory retrieval. However, cue fear memory, spatial memory, locomotor activity and anxiety levels were similar to control. These GSK3β-silenced mice also showed increased induction and maintenance of dentate gyrus long-term potentiation (DG-LTP) compared to control animals. Thus, this region-specific, targeted knockdown of GSK3β in the DG provides better understanding on the role of GSK3β in learning and memory.